Pituitary carcinomas: review of the current literature and report of atypical case. (2nd September 2020) - Todeschini, Alexandre B.; Beer-Furlan, André; Montaser, Alaa S.; Jamshidi, Ali O.; Ghalib, Luma; Chavez, Jesus A.; Lehman, Norman L.; Prevedello, Daniel M.
Abstract: Introduction: Pituitary carcinomas are poorly understood, rare entities. They are distinguished from adenomas not by histopathological features but rather by the presence of metastases. Objective: We discuss the diagnosis, mechanism of dissemination and pathogenesis based on a review of the literature and illustrated by a singular case. Case Report: A 59-year-old male presented with a dural-based posterior fossa lesion. He had been diagnosed with a pituitary chromophobe adenoma 43 years earlier that was treated at the time with surgery and radiation therapy. A presumptive diagnosis of a radiation-induced meningioma was made and surgery was recommended. At surgery the tumour resembled a pituitary adenoma. Histopathology, laboratory findings, and the patient's medical history confirmed the final diagnosis of a prolactin-secreting pituitary carcinoma. To our knowledge, this is the longest reported interval between the pituitary adenoma and metastatic lesion diagnosis (43 years). Conclusion: Management should be tailored to individual patient and may include a combination of treatments (surgery, radiation therapy, chemotherapy, and hormone-targeted therapy). Functionally active tumours may be monitored with hormone levels as tumour markers.